2018
DOI: 10.1016/j.jamcollsurg.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Probability of Positive Genetic Testing Results in Patients with Family History of Primary Hyperparathyroidism

Abstract: In addition to a family history of PHPT, male sex, age 45 years and younger, and presence of multigland disease, should prompt physicians to offer the opportunity for genetic counseling and testing, as it could influence the management of patients with PHPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…When considering young patients (< 40), one in four patients had clinical genetic testing that led to altered clinical management. The results of our clinical experience are in accordance with other studies that systematically studied archived clinical samples or patients with a family history of pHPT [19,20]. Changes in clinical care occurred in four patients with rare variants in CASR, two patients with rare variants in CDC73, and one patient with a pathogenic variant in MEN1.…”
Section: Discussionsupporting
confidence: 88%
“…When considering young patients (< 40), one in four patients had clinical genetic testing that led to altered clinical management. The results of our clinical experience are in accordance with other studies that systematically studied archived clinical samples or patients with a family history of pHPT [19,20]. Changes in clinical care occurred in four patients with rare variants in CASR, two patients with rare variants in CDC73, and one patient with a pathogenic variant in MEN1.…”
Section: Discussionsupporting
confidence: 88%
“…El Lakis et al (1) also demonstrated that activating mutations of GCM2 were associated with a greater rate of multi-glandular diseases. In our study, some patients with class 3 or 4 variants harbored parathyroid hyperplasia or multiple glandular adenomas but the lack of anatomopathological information available for many patients did not allow us to confirm this point.…”
Section: Discussionmentioning
confidence: 96%
“…It can result from a single or multiglandular lesion, adenoma, hyperplasia or much less frequently carcinoma. The prevalence of this disease is estimated around 1-7 cases per 1000 persons (1). PHPT can be either sporadic or inherited.…”
Section: Introductionmentioning
confidence: 99%
“…2 The characteristics of this patient should prompt an evaluation for genetic causes of PHPT because the factors associated with hereditary PHPT are young age at diagnosis (<40 years), the presence of syndromic features/tumors, contributory family history, and multigland disease. [1][2][3][4][5] Male sex is also a factor to consider because there is a female predominance in sporadic PHPT. 3 We support consideration of genetic testing for any patient with PHPT presenting at a young age (with the cutoff varying from <30 to 45 years or from <40 to 45 years with multigland disease), harboring syndromic features, or having a positive family history of PHPT and/or other syndromic tumors.…”
Section: Men1 Diagnosismentioning
confidence: 99%
“…This is important to recognize because hereditary disease influences prognosis, surgical strategy, and the risk of other syndromic manifestations and has important implications for family members 2 . The characteristics of this patient should prompt an evaluation for genetic causes of PHPT because the factors associated with hereditary PHPT are young age at diagnosis (<40 years), the presence of syndromic features/tumors, contributory family history, and multigland disease 1‐5 . Male sex is also a factor to consider because there is a female predominance in sporadic PHPT 3 .…”
Section: Men1 Diagnosismentioning
confidence: 99%